2022
DOI: 10.1182/blood.2021012197
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent effects of Igf2bp2 on gene regulation, function, and aging of hematopoietic stem cells in mice

Abstract: Increasing evidence links metabolism, protein synthesis, and growth signaling to impairments in the function of hematopoietic stem and progenitor cells (HSPC) during aging. The Lin28b/Hmga2 pathway controls tissue development and the postnatal downregulation of this pathway limits the self-renewal of adult vs. fetal hematopoietic stem cells (HSC). Igf2bp2 is an RNA binding protein downstream of Lin28b/Hmga2, which regulates mRNA stability and translation. The role of Igf2bp2 in HSC aging is unknown. Here, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 50 publications
4
12
0
Order By: Relevance
“…IGF2BP2 is therefore important in regulating both nonterminal and terminal differentiation. In vivo, in IGF2BP2‐knockout mice, IGF2BP2‐knockdown significantly inhibited stem cell proliferative ability and promoted stem cell differentiation (Suo et al, 2022), consistent with our conclusions. Other studies have also addressed the effects of IGF2BP2 deletion on stem cell proliferation and differentiation (Dai et al, 2015; Regué et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…IGF2BP2 is therefore important in regulating both nonterminal and terminal differentiation. In vivo, in IGF2BP2‐knockout mice, IGF2BP2‐knockdown significantly inhibited stem cell proliferative ability and promoted stem cell differentiation (Suo et al, 2022), consistent with our conclusions. Other studies have also addressed the effects of IGF2BP2 deletion on stem cell proliferation and differentiation (Dai et al, 2015; Regué et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…IGF2BP2 is therefore important in regulating both nonterminal and terminal differentiation. In vivo, in IGF2BP2-knockout mice, IGF2BP2-knockdown significantly inhibited stem cell proliferative ability and promoted stem cell differentiation (Suo et al, 2022), consistent with our conclusions.…”
Section: Srf Regulated the Cell Cycle Cell Proliferation And Ogdsupporting
confidence: 91%
“…We also found down-regulation of Igf2bp2 , which has recently been shown to be important for the function of young HSC in mice. 21 Additionally Ccnb2 along with the also upregulated gene Ifi27l1 have previously been found upregulated in HSC of IFN-treated mice. 22 We also found upregulation of Cd53 , which is involved in IL2 signaling and thus also connected to inflammation and IFN.…”
Section: Discussionmentioning
confidence: 89%
“…More recent studies using high throughput approaches have also revealed links between changes during development and ageing [10,40,49,100,101], as highlighted in epigenetic clocks [21,22,42]. Other recent studies, for example of hematopoietic stem cells in mice [102] and the aryl hydrocarbon receptor [103], further support the concept that developmental pathways influence ageing phenotypes later in life. Although these studies are encouraging, many open questions remain.…”
Section: Manipulations Of Ageing Change the Software's Runtimementioning
confidence: 86%